THE USE OF PODCASTS IN TEACHING LISTENING TO ESL STUDENTS - Ni Made Wersi Murtini (International Journal of Applied Science and Sustainable Development (IJASSD), 2022)
Listening is one of the four language skills that must be mastered by ESL students. Listening skill plays important role in communication to respond to what people speak. The present research was mainly based on the preliminary observation of 30 subjects in Semester 4A of the English Language Education Study Program which showed that most of the subjects’ listening skill was still low. Besides, the present research was intended to know whether or not the listening skill of the fourth-semester students in 4A class of the English Language Education Study Program can be improved through the use of podcasts. To achieve the objective, the researcher conducted classroom action research that was done in two cycles. Furthermore, the required data were obtained by administering the research instruments: tests and a questionnaire. The collected data were then analyzed by comparing the pre-test and post-tests, which showed significant improvements in the subjects’ mean scores from the pre-test to post-tests. Furthermore, the questionnaire results showed the subjects’ positive responses to the use of podcasts in teaching Listening. Based on the results of the research instruments, it could be concluded that the listening skill of the students in 4A Class of the English Language Education Study Program can be improved through the use of a Podcast.